(untitled) (International Journal of Agriculture and Sustainable Development, 2021)
Rice production in Sheikhupura Punjab Pakistan will be examined in this study. Farmers in Pakistan’s distant rural areas aren’t using their resources effectively. As a result, inefficient decisions are made that waste time and money. Pertinent data were used to analyze rice production. Agricultural inputs such as fertilizer as well as labor, capital, training, and rice price, all have a substantial impact on the District’s ability to produce rice. The outcomes of this study point to the importance of each of these elements in rice production. Rice production is hampered by a lack of physical capital, technical skills, and the advancing age of farmers. Finally, it is advised that the government take specific measures to improve water systems, farmer training, input availability, and loan access in order to raise rice output.